O ensino de frações na contextualização de problemas utilizando jogo dominó nas turmas da 3ª etapa do ensino de jovens e adultos - EJA - Mafra, Samir Pedro de Abreu (2019)
This paper is divided into three chapters. The first one addresses the main theoretical concepts of the foundation for the development of this work. The second chapter presents the methodological aspects related to the application of the project. The third chapter shows the results obtained through data analysis achieved with the application of dominoes game. As well as the results of activities performed during the research. This project has as a general objective: to evaluate how the use of ludic games are important important facilitating tools for the teaching of fractions in the discipline of mathematics for students of elementary education of the 3rd stage of EJA in a public school in public school in the municipality of Presidente Figueiredo. Having thus the specific objectives: To teach a theoretical class on fractions to a EJA class; To teach to teach a ludic class with the use of fractions dominoes on the same theme; and To identify the difficulties that the student has in relation to the methodology applied by the teacher in the classroom. However this project aims to contribute to the improvement of the teaching and learning in the contents of fractions and the four mathematical operations of students of the 3rd Stage of Youth and Adult Education - YAE through the ludicity by using of the game of fractions dominoes.